1997
DOI: 10.1049/el:19970635
|View full text |Cite
|
Sign up to set email alerts
|

Circular synthetic aperture radar (C-SAR) systemfor ground-based applications

Abstract: EDLINGER, J.: 'A GaAs/AlGaAs refractometer platform for integrated optical sensing applications', to be published in Sens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In this way, the total slow-time is the ratio of the scanning time to the pulse duration (i.e., 1,304 slow-times during the experiment). The angle resolution (δ ang ) is defined as the ratio of the scanning angle to the slow-time, mathematically, δ ang = π/ST The cross-range resolution depends on the object's range [8] and can be calculated as:…”
Section: Cross-range Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the total slow-time is the ratio of the scanning time to the pulse duration (i.e., 1,304 slow-times during the experiment). The angle resolution (δ ang ) is defined as the ratio of the scanning angle to the slow-time, mathematically, δ ang = π/ST The cross-range resolution depends on the object's range [8] and can be calculated as:…”
Section: Cross-range Resolutionmentioning
confidence: 99%
“…Although this model is theoretically optimal, it suffers from many practical limitations for use in ground-based applications. These limitations are solved by the model presented in [8], where the radar sensors exhibit a semi-circular trajectory whose circumference is adjacent to the scanning area, with continuous wave stepped frequency signals to detect objects with a high Radar Cross Section (RCS) at distances below 4 meters in a clutter-free environment. However, the problem associated with this model, is that it can only detect high RCS objects in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Research into CSAR began in the early 1990s [12][13][14]. Soumekh first proposed the imaging mode and echo signal time-domain model of CSAR in 1996, and also proposed the CSAR imaging algorithm based on wavefront reconstruction [15].…”
Section: Introductionmentioning
confidence: 99%
“…After H. Klausing had made a systematical analysis on CSAR [1], many scholars have issued their research results about CSAR. A. Broquet et al proposed a CSAR model in which an antenna is fixed at the end of a boom rotating about a vertical mast of certain height [2]. H. Rudolf et al suggested a combination of linear and circular SAR to realize 3-Dimentional imaging [3].…”
Section: Introductionmentioning
confidence: 99%